Strategies for Implementing LTE/LTE-A Wireless Networks - Ahmed A. Alsabri (المجلة الأفروآسيوية للبحث العلمي, 2024)
LTE-Advanced builds upon the foundational features of LTE, such as network architecture and radio interface, by incorporating additional enhancements to further optimize system performance. One of the critical and complex challenges presented by LTE technology is managing multiple users who require high data rates within a limited bandwidth in the same geographical area, all while maintaining low latency. To address this, multiple access techniques are employed, which allocate portions of the total system resources to each User Equipment (UE), enabling efficient sharing of available bandwidth. To significantly enhance system performance, particularly by increasing the spectral efficiency of the wireless interface and thereby expanding system capacity, the development of advanced resource allocation algorithms for scheduling is imperative. This paper provides a concise review of LTE and LTE-Advanced, with a particular focus on Carrier Aggregation techniques and downlink scheduling methodologies.